Predictive factors and oncological outcomes of persistently elevated prostate-specific antigen in patients following robot-assisted radical prostatectomy. Issue 1 (March 2017) - Kumar, Anup; Samavedi, Srinivas; Mouraviev, Vladimir; Bates, Anthony; Coelho, Rafael; Rocco, Bernardo; Patel, Vipul
Abstract Our aim was to evaluate factors associated with persistently elevated prostate-specific antigen (PSA) and biochemical recurrence following robotic-assisted radical prostatectomy (RARP). The study population (N = 5300) consisted of consecutive patients who underwent RARP for localized prostate cancer by a single surgeon (VP) from January 2008 through July 2013. A query of our Institutional Review Board-approved registry identified 162 men with persistently elevated PSA (group A), defined as PSA level ≥0.1 ng/ml at 6 weeks after surgery, who were compared with rest of the cohort group having undetectable PSA, group B (<0.1 ng/ml). A univariate and multivariate logistic regression analysis was used to evaluate the significant association between various variables and the following: (1) persistently elevated PSA, (2) BCR (PSA value ≥0.2 ng/ml) on follow-up in the persistent PSA group. On multivariate analysis, only the following parameters were significantly associated with persistent PSA after RARP—preoperative [PSA >10 ng/ml (p = 0.01), Gleason Score ≥8 (p = 0.001) and clinical stage(p = 0.001)]; postoperative [pathologic stage (p = 0.001), extraprostatic extension (EPE, p = 0.01), lymph node positivity (p = 0.001), positive surgical margin (PSM, p = 0.02), Gleason score (p = 0.01) and tumor volume percent (p < 0.001)]. The mean follow-up was 38.1 months. The BCR was significantly higher in group A as compared to group B(52.47 vs 7.9 %) respectively;p = 0.01). The mean time to BCR was significantly lesser in group A as compared to group B(8.9 vs 21.1 months respectively;p = 0.01). The BCR-free survival rates at 1 year and 3 years were significantly lower statistically in the persistent PSA group in comparison to other groups (69.7 vs 97.3 % and 48.5 vs 92.1 %, respectively;p = 0.01). On multivariate logistic regression analysis in patients with persistent PSA on follow-up, preoperative PSA >10 ng/ml, postoperative Gleason score ≥8, postoperative stage ≥pT3, positive pelvic lymph nodes, PSM >3 mm and post-RARP PSA doubling time (DT) <10 months (p < 0.001) were significantly associated with BCR. In patients after RARP, factors associated with aggressive disease (high preoperative PSA, Gleason score ≥8, stage ≥T3, PSM, high tumor volume percent and EPE) predict PSA persistence. Although these patients with persistent PSA after RARP are more likely to have BCR and that too earlier than those patients with undetectable PSA after RARP, a significant proportion of these patients (47.53 %) remain free of BCR. This subset of patients is associated with these favorable parameters (preoperative PSA <10 ng/ml, post-RARP PSA DT ≥10 months, postoperative Gleason score <8, pathologic stage <pT3, PSM <3 mm and no lymph node involvement), thus potentially not requiring any adjuvant treatment.